Analysis of risk factors for the increased incidence of gallstone caused by hepatectomy: A retrospective case–control study - Zhou, Jiangmin; Chen, Lin; Zhang, Zhiwei; Wu, Biao (Frontiers in Surgery, 2023)
Background An increased risk of gallstone has been observed in patients undergoing hepatectomy. This study attempted to analyze the risk factors of gallstone after hepatectomy. Methods: From January 2013 to December 2016, Clinical data of 1452 eligible patients who underwent hepatectomy were consecutively reviewed. According to the imaging including gallbladder ultrasound, CT, and MRI, all patients were divided into gallstone group and non-gallstone group. Univariate and multivariate logistic regressions were used to select indicators associated with gallstone formation among patients after hepatectomy. Results: In the total sample of included patients, there were 341 patients with gallstone and 1147 patients without gallstone. The incidence of gallstones was (341/1452) 23.5%. The incidence of gallstones in primary liver cancer group was higher than benign liver tumor group (25.7% versus 18.9%, P=0.004). Univariate and multivariate logistic regression analysis showed that female gender, high body mass index (BMI), tumor located in S5 and severe postoperative complication were factors related to gallstone in patients with benign tumor of liver after hepatectomy. Besides, Child-Pugh B, low albumin, liver cirrhosis, and transcatheter arterial chemoembolization (TACE) after recurrence were factors related to gallstone in patients with primary liver cancer after hepatectomy. Conclusions: Hepatectomy increased the risk of gallstone in both benign or malignant liver tumor, especially, when tumor was located in S5. TACE further increased the risk of gallstone in patients with postoperative recurrence.